1986
DOI: 10.1002/er.4440100204
|View full text |Cite
|
Sign up to set email alerts
|

A study of the operating parameters in a water-lithium bromide absorption cooler

Abstract: Experiments were carried out to study the effect of changes in operating conditions in order to optimize the performance of a water‐lithium bromide absorption cooler. It was shown that the most significant parameter is the generator temperature. The higher the generator temperature, the higher the coefficient of performance. The flow ratio is also an important design and optimizing parameter. An increase in flow ratio reduces the required generator temperature at the expense of a reduction in coefficient of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…For the lithium-iodide ternary system, the coefficient of performance values obtained were comparable with values for lithium-bromide/water systems (Eisa et al, 1986). The advantage of a higher solubility should be analysed in more detail in order to fix the limiting values of the generator temperature.…”
Section: Discussionmentioning
confidence: 53%
“…For the lithium-iodide ternary system, the coefficient of performance values obtained were comparable with values for lithium-bromide/water systems (Eisa et al, 1986). The advantage of a higher solubility should be analysed in more detail in order to fix the limiting values of the generator temperature.…”
Section: Discussionmentioning
confidence: 53%
“…experimentally performed operating parameter to satisfy for the operating process condition in the absorption system. To predict results from changing working parameter on the performance of the system [3]. In the vapour absorption system is influenced by the generator temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Eisa and Holland [3] performed an experimental investigation to study the effect of changes in operating conditions on the performance of LiBr-H 2 O absorption cooler for optimization purposes. They found that the most significant parameter affecting COP is the desorber temperature.…”
Section: Introductionmentioning
confidence: 99%